The limit to exercise tolerance in humans: mind over muscle? - Marcora, S. M.; Staiano, W. (European Journal of Applied Physiology, 2010)
In exercise physiology, it has been traditionally assumed that high-intensity aerobic exercise stops at the point commonly called exhaustion because fatigued subjects are no longer able to generate the power output required by the task despite their maximal voluntary effort. We tested the validity of this assumption by measuring maximal voluntary cycling power before (mean +/- SD, 1,075 +/- 214 W) and immediately after (731 +/- 206 W) (P < 0.001) exhaustive cycling exercise at 242 +/- 24 W (80% of peak aerobic power measured during a preliminary incremental exercise test) in ten fit male human subjects. Perceived exertion during exhaustive cycling exercise was strongly correlated (r = -0.82, P = 0.003) with time to exhaustion (10.5 +/- 2.1 min). These results challenge the long-standing assumption that muscle fatigue causes exhaustion during high-intensity aerobic exercise, and suggest that exercise tolerance in highly motivated subjects is ultimately limited by perception of effort. Auch mit Volltext über: https://www.researchgate.net/publication/41896455_The_limit_to_exercise_tolerance_in_humans_mind_over_muscle